GCP21: a global cassava partnership for the 21st century - Fauquet, Claude M.; Tohme, Joseph M. (Burleigh Dodds Science Publishing Limited, 2017)
Since 1998, cassava has outperformed all the world’s major crops in relative production increase. It is also recognized as being resilient to climate change. Its global average yield, however, is only 13 Mt/ha, compared to a potential of at least 65 Mt/ha, partly due to the impact of pests and diseases. The cassava community needs to improve production, processing and market development to keep its derived food products affordable for global populations. This effort will require a significant increase in research and development (R&D) investment, while speeding up the improvement of cassava value chains – from production in the field to consumption on the plate. This is what the Global Cassava Partnership for the 21st century aims to realize by advocating for cassava to change mindsets, identifying gaps in R&D value chains, and accelerating the flow of information about cassava.